The effect of a serious game on aviation vocabulary acquisition - Nazmi Dinçer; Rabia Dinçer (Serious Games Society, 2021)
Having proficiency in the standard aviation phraseology specified by International Civil Aviation Organization (ICAO) is of great importance for prospective pilots in communication with air traffic controllers and other pilots. The ambiguity in the standard phraseology could be a disaster for the flight crews. That's why; serious thought has been given at the policy of improving the precise communication in aviation. However, it remains unclear whether the serious game-based flight simulations can enhance the vocabulary intake of the learners who invest the majority of their time in studying the standard aviation phraseology. There is also a dearth of research pertaining to the association between serious gaming and aviation phraseology. The advancement of the technology has exponentially expanded the digital games and therefore began to be widely used in education. The current study thus sets out to investigate the effect of a serious simulation game X-Plane 11 offering invaluable learning experience on aviation vocabulary acquisition. This investigation takes the form of a quasi-experimental mixed-method research by retrieving convenience sampling (15 subjects in experimental group, 15 subjects in control group). The findings indicated that there had been strong evidence of the positive effects of serious gaming on the learners' outcome. Following the integration of the serious game, a significant increase with the medium effect size in the experimental group was recorded. This finding was also echoed by the majority of the interviewees who unanimously emphasized that the game was beneficial and motivating for language learning despite the minority challenges triggered by the level of language, hardware, and software types.